2016
DOI: 10.1038/sc.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk in people with spinal cord injury: is there a possible association between reduced lung function and increased risk of diabetes and hypertension?

Abstract: This study showed that there might be a significant relationship between reduced lung function and the risk of DM and hypertension in people with SCI. Therefore, systematic measurement of these parameters should be performed in the routine clinical follow-up of SCI patients. Once reduced lung parameters are determined, the higher risk for developing hypertension and DM should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Vascular and respiratory adaptations can occur as soon as 6 weeks after injury 9 . Chronic SCI can result in maladaptive blood pressure regulation and respiratory deficits leading to hypotension, bradycardia, dyspnea, and impaired cough that together may predict the development of cardiovascular disease 7, 1014 . Higher SCI levels with more complete neurological lesions demonstrate greater cardiovascular and pulmonary functional deficits; however, even incomplete SCI lesions as low as L 4 should be considered as risk factors for cardiopulmonary disability as they still exhibit deficits from functional impairment due to accelerated aging, lifestyle factors, and decreased mobility 7, 1517 .…”
Section: Introductionmentioning
confidence: 99%
“…Vascular and respiratory adaptations can occur as soon as 6 weeks after injury 9 . Chronic SCI can result in maladaptive blood pressure regulation and respiratory deficits leading to hypotension, bradycardia, dyspnea, and impaired cough that together may predict the development of cardiovascular disease 7, 1014 . Higher SCI levels with more complete neurological lesions demonstrate greater cardiovascular and pulmonary functional deficits; however, even incomplete SCI lesions as low as L 4 should be considered as risk factors for cardiopulmonary disability as they still exhibit deficits from functional impairment due to accelerated aging, lifestyle factors, and decreased mobility 7, 1517 .…”
Section: Introductionmentioning
confidence: 99%
“…Reduced lung function is associated with a diminished capacity of maximum oxygen uptake, which is considered to be the best measure of cardiorespiratory fitness and physical exercise capacity [28]. Despite these diabetes-related reductions in the ability to oxygenate and deliver blood to peripheral tissues, some studies have found that VO 2 max is not different between subjects with type I diabetes and subjects without diabetes when matched for age, sex, body composition, and physical activity [29,30]. In this current research among University students, respiratory functions (vital capacity, forced vital capacity and forced expiratory volume) of those not at risk was higher than those at risk, showing that diabetes may impair lung functions.…”
Section: Cardiorespiratory Functionmentioning
confidence: 99%
“…CVD risk prediction scoring systems such as Framingham risk score (FRS) or the HEART score have been developed combining known CVD risk determinants, and these scores are widely used for risk stratification in the general population [6,7]. However, the determinants of increased CVD risk in SCI have not been fully elucidated, and the use of such prediction models in SCI have been rarely studied in the literature [8][9][10]. FRS may underestimate the CVD disease risk in people with SCI [8][9][10] as this scoring system does not include SCI-specific risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, the determinants of increased CVD risk in SCI have not been fully elucidated, and the use of such prediction models in SCI have been rarely studied in the literature [8][9][10]. FRS may underestimate the CVD disease risk in people with SCI [8][9][10] as this scoring system does not include SCI-specific risk factors. The level of injury may be an additional non-modifiable factor that may aggravate CVD risk and, therefore, a potential factor to consider in the development of SCI-specific CVD risk screening tools.…”
Section: Introductionmentioning
confidence: 99%